Categoricity, Variation, and Gradience in Sambla Balafon Segmental Encoding - McPherson, Laura (Frontiers in Communication, 2021)
This paper analyzes the musical surrogate encoding of Seenku (Mande, Burkina Faso) syllable structure on the balafon, a resonator xylophone used by the Sambla ethnicity. The elements of syllable structure that are encoded include vowel length, sesquisyllabicity, diphthongs, and nasal codas. Certain elements, like vowel length and sesquisyllabicity, involve categorical encoding through conscious rules of surrogate speech, while others, like diphthongs and nasal codas, vary between being treated as simple or complex. Beyond these categorical encodings, subtler aspects of rhythmic structure find their way into the speech surrogate through durational differences; these include duration differences from phonemic distinctions like vowel length in addition to subphonemic differences due to phrasal position. I argue that these subconscious durational differences arise from a “phonetic filter”, which mediates between the musician’s inner voice and their non-verbal behavior. Specifically, syllables encoded on the balafon may be timed according to the perceptual center (p-center) of natural spoken rhythm, pointing to a degree of phonetic detail in a musician’s inner speech.